Evaluation and simulation of nitrogen mineralization of paddy soils in Mollisols area of Northeast China under waterlogged incubation. - Yuling Zhang; Wenjing Xu; Pengpeng Duan; Yaohui Cong; Tingting An; Na Yu; Hongtao Zou; Xiuli Dang; Jing An; Qingfeng Fan; Yulong Zhang (PLoS ONE)
Background Understanding the nitrogen (N) mineralization process and applying appropriate model simulation are key factors in evaluating N mineralization. However, there are few studies of the N mineralization characteristics of paddy soils in Mollisols area of Northeast China. Materials and methods The soils were sampled from the counties of Qingan and Huachuan, which were located in Mollisols area of Northeast China. The sample soil was incubated under waterlogged at 30°C in a controlled temperature cabinet for 161 days (a 2: 1 water: soil ratio was maintained during incubation). Three models, i.e. the single first-order kinetics model, the double first-order kinetics model and the mixed first-order and zero-order kinetics model were used to simulate the cumulative mineralised N (NH4+-N and TSN) in the laboratory and waterlogged incubation. Principal results During 161 days of waterlogged incubation, the average cumulative total soluble N (TSN), ammonium N (NH4+-N), and soluble organic N (SON) was 122.2 mg kg-1, 85.9 mg kg-1, and 36.3 mg kg-1, respectively. Cumulative NH4+-N was significantly (P < 0.05) positively correlated with organic carbon (OC), total N (TN), pH, and exchangeable calcium (Ca), and cumulative TSN was significantly (P < 0.05) positively correlated with OC, TN, and exchangeable Ca, but was not significantly (P > 0.05) correlated with C/N ratio, cation exchange capacity (CEC), extractable iron (Fe), clay, and sand. When the cumulative NH4+-N and TSN were simulated, the single first-order kinetics model provided the least accurate simulation. The parameter of the double first-order kinetics model also did not represent the actual data well, but the mixed first-order and zero-order kinetics model provided the most accurate simulation, as demonstrated by the estimated standard error, F statistic values, parameter accuracy, and fitting effect. Conclusions Overall, the results showed that SON was involved with N mineralization process, and the mixed first-order and zero-order kinetics model accurately simulates the N mineralization process of paddy soil in Mollisols area of Northeast China under waterlogged incubation.